2012
DOI: 10.1111/j.1750-3841.2012.02633.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Electron Microscopic Analysis Showing Structural Changes to Bacterial Cells Treated with Electrolyzed Water and an Acidic Sanitizer

Abstract: An understanding of the method in which E-water and an acidic sanitizer cause injury to E. coli and L. innocua would be helpful in selecting an effective chemical agent as a food safety tool. This will allow a scientist to target similar microorganisms such as food borne bacteria with structures that are vulnerable to the sanitizer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 34 publications
2
13
0
1
Order By: Relevance
“…Close examination of both images, Salmonella Typhimurium SL 1344 treated with LB-spent culture supernatant and our C. sakazakii treated with Narine-CCFE, showed the same altered cell envelope. Feliciano et al (2012) reported that inactivated bacterial cells showed a less defined envelope along with a rugged cell wall, suggesting that inactivated cells appeared due to reduced integrity of the cell envelope and aggregation of cytoplasmic components.…”
Section: Resultsmentioning
confidence: 99%
“…Close examination of both images, Salmonella Typhimurium SL 1344 treated with LB-spent culture supernatant and our C. sakazakii treated with Narine-CCFE, showed the same altered cell envelope. Feliciano et al (2012) reported that inactivated bacterial cells showed a less defined envelope along with a rugged cell wall, suggesting that inactivated cells appeared due to reduced integrity of the cell envelope and aggregation of cytoplasmic components.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, our results were also supported by Skrivanova et al (2006), who found that AEW was more effective against planktonic Gram-positive bacteria than planktonic Gram-negative bacteria. One explanation of these phenomena is that the transport of ions across the cell membrane of Gram-positive bacteria is more vulnerable to interference (Skrivanova et al, 2006; Feliciano et al, 2012; Chen et al, 2014). In addition, this apparent discrepancy could partly be explained by the different structural composition of EPS in different biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…AEW is commonly used in the agricultural and medical fields as a disinfectant for farm and food hygiene (Fabrizio and Cutter, 2004;Northcutt et al, 2007;Guentzel et al, 2008;Cao et al, 2009;Park et al, 2009;Lu et al, 2010;Rahman et al, 2010Rahman et al, , 2011. It is also widely used for the disinfection of medical instruments such as dialyzers (Tanaka et al, 2000), endoscopes (Lee et al, 2004), and dentures (Nagamatsu et al, 2001) because of its potent antimicrobial potential (Kiura et al, 2002;Sharma and Demirci, 2003;Nisola et al, 2011;Rodriguez-Garcia et al, 2011;Feliciano et al, 2012). AEW has potent oxidative power in relation to its antimicrobial potential.…”
Section: Introductionmentioning
confidence: 99%